Poly(acrylonitrile/methyl acrylate) copolymers and clay nanocomposites : structural and property relationships - Zengeni, Eddson (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2009.